Recurrent Fulminant Tumefactive Demyelination With Marburg-Like Features and Atypical Presentation: Therapeutic Dilemmas and Review of Literature - Vakrakou, Aigli G.; Tzanetakos, Dimitrios; Argyrakos, Theodore; Koutsis, Georgios; Evangelopoulos, Maria-Eleptheria; Andreadou, Elisabeth; Anagnostouli, Maria; Breza, Marianthi; Tzartos, John S.; Gialafos, Elias; Dimitrakopoulos, Antonios N.; Velonakis, Georgios; et al. (Frontiers in Neurology, 2020)
Atypical forms of demyelinating diseases with tumor-like lesions and aggressive course represent a diagnostic and therapeutic challenge for neurologists. Herein, we describe a 50-year-old woman presenting with subacute onset of left hemiparesis, memory difficulties and headache. Brain MRI revealed a tumefactive right frontal-parietal lesion with perilesional edema, mass effect and homogenous post-contrast enhancement, along with other small atypical lesions in the white-matter. Brain biopsy of cerebral lesion ruled out lymphoma or any other neoplastic process and patient placed on corticosteroids with complete clinical/radiological remission. Two years after disease initiation, there was disease exacerbation with reappearance of the tumor-like mass. The patient initially responded to high doses of corticosteroids but soon became resistant. Plasma-exchange sessions were not able to limit disease burden. Resistance to therapeutic efforts led to a second biopsy that showed perivascular demyelination, predominantly consisting of macrophages, with a small number of T and B lymphocytes, and the presence of reactive astrocytes, typical of Creutzfeldt-Peters cells. The patient received high doses of cyclophosphamide with substantial clinical/radiological response but relapsed after 7-intensive cycles. She received 4-weekly doses of rituximab with disease exacerbation and brainstem involvement. She eventually died with complicated pneumonia. We present a very rare case of recurrent tumefactive demyelinating lesions, with atypical tumor-like characteristics, with initial response to corticosteroids and cyclophosphamide, but subsequent development of drug-resistance and unexpected exacerbation upon rituximab administration. Our clinical case raises therapeutic dilemmas and points to the need for immediate and appropriate immunosuppression in difficult to treat tumefactive CNS lesions with Marburg-like features.